2019
DOI: 10.1172/jci129143
|View full text |Cite
|
Sign up to set email alerts
|

Gene loci associated with insulin secretion in islets from nondiabetic mice

Abstract: Genetic susceptibility to type 2 diabetes is primarily due to β cell dysfunction. However, a genetic study to directly interrogate β cell function ex vivo has never been previously performed. We isolated 233,447 islets from 483 Diversity Outbred (DO) mice maintained on a Western-style diet, and measured insulin secretion in response to a variety of secretagogues. Insulin secretion from DO islets ranged greater than 1000-fold even though none of the mice were diabetic. The insulin secretory response to each sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 67 publications
2
83
0
Order By: Relevance
“…Common forward genetics analyses include quantitative trait locus (QTL) mapping (linkage studies applied on related individuals) and genome-wide association study (GWAS) (association studies using a large number of related or unrelated individuals), which are widely used to map the genetic loci that correlate with a particular trait, ranging from phenotypes, metabolites, proteins, transcripts, to epigenetic markers [76,77]. In recent years, studies have been performed to study the genes involved in the various diseases and complex traits, including insulin secretion [88], diabetes [37], hepatic steatosis or fibrosis [43,44], blood pressure [89], and bone density [90].…”
Section: Trends Trends In In Genetics Geneticsmentioning
confidence: 99%
“…Common forward genetics analyses include quantitative trait locus (QTL) mapping (linkage studies applied on related individuals) and genome-wide association study (GWAS) (association studies using a large number of related or unrelated individuals), which are widely used to map the genetic loci that correlate with a particular trait, ranging from phenotypes, metabolites, proteins, transcripts, to epigenetic markers [76,77]. In recent years, studies have been performed to study the genes involved in the various diseases and complex traits, including insulin secretion [88], diabetes [37], hepatic steatosis or fibrosis [43,44], blood pressure [89], and bone density [90].…”
Section: Trends Trends In In Genetics Geneticsmentioning
confidence: 99%
“…To demonstrate information captured by LECIF for translation of biological findings between mouse and human in a phenotypic context, we analyzed mouse insulin secretion quantitative trait loci (QTL) and human diabetes GWAS variants 59 . Previously, it was shown that human regions syntenic to the mouse insulin secretion QTL were enriched for the human diabetes GWAS variants.…”
Section: Lecif Score Highlights Regions Within Mouse Quantitative Tramentioning
confidence: 99%
“…* and *** denote Bonferroni-corrected p-values for the LECIF score annotation's enrichment below 0.05 and 0.001, respectively. c. Distribution of mean LECIF score of non-overlapping 1-kb human genomic windows identified as lying within a mapped mouse insulin scretion QTL or containing a human diabetes GWAS variant or both 59 .…”
Section: Lecif Score Highlights Regions With Conserved Differential Mmentioning
confidence: 99%
“…Zfp148 was recently implicated in glucose tolerance and insulin secretion from pancreatic islets in mice (Keller et al 2019). However, follow-up studies on insulin sensitivity here revealed no metabolic impact of ZFP30 loss, nor did we observe a significant difference in Pparg2 expression in the white adipose tissues of our mice.…”
Section: Discussionmentioning
confidence: 99%